ANALISIS PERFORMA DAN DESAIN JARINGAN KOMPUTER MENGGUNAKAN TOP-DOWN NETWORK DESAINSTUDI KASUS PADA CV. MERAH PUTIH - Ikhsanto, Muhammad Nur (Jurnal Informatika, 2016)
Analysis of computer networking is very important and necessary to help improve network performance. Many companies are designed their networks are not in accordance with its business goals, so the performance of the existing network of the company is not as they expected. Therefore required an analysis on existing computer network within the company, both in terms of performance as well as network design. Existing network designs are closely related to the performance of the network. In this study the parameters that exist in a computer networking such as delay, jitter, bandwidth, packet utilization, packet loss and throughput will be measured to determine the performance of the network and then these parameters are used as information to redesign the network to get better network performance and generate more structured network design according to the needs of the company.Â Keyword : network performance, Top-Down Network Desain, delay, jitter, bandwidth, paket loss, thoughput, network design.